A significant decreased in the frequency of Clostridioides difficile infection at the Italian Hospital of Desio over the last decade. (August 2021) - Intra, J.; Carcione, D.; Sarto, C.; Brambilla, P.
Abstract: Clostridiodes difficile infection (CDI) is the most important cause of healthcare-associated diarrhea. The decreasing trend of CDI from 15% to 4% observed at the Italian Hospital of Desio over a 10-year period is due to prevention strategies. Our data highlight the importance of surveillance studies to control CDI. Highlights: C. difficile infection: the most important cause of healthcare-associated diarrhea. Prevention strategies implemented from 2010. A decreasing trend of CDI from 15% to 4% was observed in our hospital. The importance of surveillance studies to improve and control CDI.